SUSTAINABILITY MANAGEMENT MODEL OF MICRO, SMALL AND MEDIUM-SIZED ENTERPRISES BASED ON THE ENTREPRENEURSHIP ECOSYSTEM IN THE MIMIKA REGION, CENTRAL PAPUA - Nurdin, Djayani; Husnah, Husnah; Haryanti, Tuti; Latifah, Ayi; Krisnamurti, Reza Mahendra; Bidin, Cici Rianty K (Universitas Tadulako, 2024)
This study aims to build a sustainability model for independent workforce in the Mimika Region, grounded in the identification of resources, program impacts, problems encountered, and the possibility for independent workforce development within an entrepreneurial ecosystem. This study employs a qualitative methodology utilizing a case study approach and descriptive analysis. The data used in this study were obtained through several data collection techniques, namely: questionnaires, in-depth interviews and FGDs. The collected data were evaluated through descriptive methods to ascertain the parameters that affect the sustainability of independent workforce. The study's results indicate that the sustainability of independent workforce can be attained through an entrepreneurial environment, facilitated by collaboration with universities and innovation incubation centers. The entrepreneurial ecosystem fosters economic growth and community welfare by promoting innovation, collaboration, and resource sharing among diverse stakeholders. This ecosystem fosters an atmosphere conducive to entrepreneurial endeavors, hence resulting in job creation and sustainable enhancement of the quality of life in the Mimika Region.